REKONSTRUKSI AKTIVITAS DAKWAH MELALUI MEDIA MASSA - Rahmat Ramdhani (JURNAL ILMIAH SYI'AR, 2017)
The existence of da’wah in this contemporary era is faced with the complexity of problems and challenges. This is inseparable from the progressive dynamics of society and the shift of orientation, from agrarian society with simplicity and simplicity into an individualized society based on information technology. Given the activity of da’wah is inseparable from the community, then its development must be directly proportional to the development of society. During this da’wah activities are still left behind with the development and changes in society, especially in the utilization of mass media in da’wah. This background that underlies the author in reconstructing the activities of Islamic da’wah through mass media, so that it can be used as a theoretical-normative basis to be practical-applicative.